Investigating the Structure and Dynamics of Apo‐Photosystem II. Issue 16 (21st June 2019) - Han, Ruocheng; Rempfer, Katharina; Zhang, Miao; Dobbek, Holger; Zouni, Athina; Dau, Holger; Luber, Sandra
Abstract: Photosynthetic water oxidation is a model for future technologies employing solar energy to split water into hydrogen and oxygen. Natural water oxidation is carried out by a special manganese catalyst, the water‐oxidizing complex (WOC), located in photosystem II (PSII) of cyanobacteria, algae, and plants. Hence, there is great interest in the molecular structure as well as structural changes during catalytic activity and assembly/disassembly of the WOC. In particular, the light‐driven assembly during photosystem II repair under physiological conditions is poorly understood, and structural information about manganese depleted PSII (apo‐PSII) is required as a starting point for improving this understanding. Recently Zhang et al. (eLife 2017;6:e26933) showed that the cavity harboring the WOC in PSII remains largely intact upon manganese‐depletion and suggested that deprotonation of hydrogen‐bonding pairs enables the charge‐compensated insertion of the manganese cations without any major change of the cavity structure. By computational methods we have further investigated the structure of apo‐PSII and show how it can be stabilized by protons localized at the terminal carboxylate groups inside the remaining cavity. Ab ‐ initio molecular dynamics simulations suggest that not more than two water molecules fill the void left by manganese depletion. Abstract : Different protonation patterns of the photosystem II without the water‐oxidizing complex (apo‐PSII) have been investigated computationally. Static and dynamic density functional theory simulations show which proton distributions lead to agreement with experimental X‐ray data, thus paving the way for further investigations of the photoassem‐ bly process of photosystem II.